PENGGUNAAN METODE THINK-PAIR-SHARE DALAM MENINGKATKAN PEMAHAMAN SISWA MELALUI PEMBELAJARAN PKn - Uswatun Hasanah (Educare : Jurnal Ilmu Pendidikan, 2022)
This study aims to analyze and examine the application of Civics learning using the Think-Pair-Share method in increasing student understanding. This research uses a qualitative approach. This research was conducted at a formal institution located in the probolinggo area of ​​MI Raudlatul faizin Hamlet of Karanganyar Sokaan Krejengan Probolinggo. Data analysis techniques include data reduction, data display, and conclusions. The results showed that the institution first used the Think-Pair-Share method in Civics learning. The second presentation is carried out using the initial framework of activities, the application of the Think-Pair-Share learning model, and Activity Evaluation. The implications obtained in the application of Civics learning using the Think-Pair-Share Model can develop students' understanding of Civics lessons which are carried out with the tricks and creativity of the teacher using the Think-Pair-Share learning model.